The Expanding Armamentarium of Innovative Bioengineered Strategies to Augment Cardiovascular Repair and Regeneration - Elde, Stefan; Wang, Hanjay; Woo, Y. Joseph (Frontiers in Bioengineering and Biotechnology, 2021)
Cardiovascular disease remains the leading cause of death worldwide. While clinical trials of cell therapy have demonstrated largely neutral results, recent investigations into the mechanisms of natural myocardial regeneration have demonstrated promising new intersections between molecular, cellular, tissue, biomaterial, and biomechanical engineering solutions.